Atividade de voo de Plebeia aff. flavocincta Apidae, Meliponini e sua relaçao com fatores abióticos - Oliveira, Fabiano Luiz de (Universidade Federal Rural do Semi-Árido, 2016)
Stingless bee species that occur in the Brazilian semiarid region are adapted to the hot and dry climate of the region. Additionally, the availability of floral resources varies greatly throughout the year. Thus, climatic factors associated with variation in resource availability may be important determinants for the external activities of stingless bee colonies in this ecoregion. The foraging activities are critical for the maintenance of colonies, since they are important to supply the colonies with food (pollen and nectar) and materials for construction and defense of the colony (resin). In the present study, I analyzed the abiotic conditions, mainly external ambient temperature, nest-internal temperature and relative humidity, and investigated whether and to which extent these variables are related to and interact with the foraging activity of Plebeia aff. flavocincta in the Brazilian semiarid region, where these bees naturally occur. The peak foraging activity of the bees was in a temperature range between 32-34°C. The colonies of Plebeia aff. flavocincta intensified their nectar and pollen collection in months with elevated precipitation, when resources in the environment were abundant. In the dry period, by contrast, foraging activity was genearlly low. The colonies adjusted their foraging activity to the given climatic conditions, which points to behavioral adaptations of this bee species to the environmental unpredicatbility of the Brazilian semiarid region
Flight activity of Plebeia aff. flavocincta (APIDAE, MELIPONINI) and its relationship with abiotic factors
Keywords: Bees; Flight activity - bees; Abiotic conditions; Caatinga; Thermal window; Abelha; Atividade de voo - abelhas; Condições abióticas; Caatinga; Janela térmica; CIENCIAS AGRARIAS::MEDICINA VETERINARIA